United States proposal for a United and Associated Nations Stabilization Fund. (London : His Majesty's Stationery Office, 1943)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Wereldoorlog 2; Naoorlogse Politiek; economische politiek